Easy Steps to Build a Digital Business Showcase by Creating a Simple Website - Nasirul Haq, Muhammad; Khalisah Hasna Naila Shifa; Agung Firmansyah; Fadli Indra Guci; Rully Mujiastuti; Sitti Nurbaya Ambo; Popy Meilina; Yana Adharani; Nurvelly Rosanti; Sukmawandana Gilang Nurmawan (Edumedia Solution, 2026)
The digital divide phenomenon in the era of the Industrial Revolution 4.0 remains a major barrier to the growth of Micro, Small, and Medium Enterprises (MSMEs). Many business actors still rely on manual showcases or social media platforms that are vulnerable to algorithm changes. This community service activity aims to provide a solution through a Webinar and Workshop program entitled “Rakit Etalase Digitalmu,” which introduces websites as professional and independent digital showcases. The program was implemented in two stages: community education (webinar) and technical training (workshop) covering basic HTML, CSS, and JavaScript. Evaluation through pre-tests and post-tests showed an average correct response rate of 86% in the pre-test and 82% in the post-test, which does not yet indicate a quantitative improvement, although participants’ understanding remained in the good category. Feedback results revealed a high level of participant satisfaction, with an average rating of approximately 4.2 out of 5, and demonstrated meaningful gains in knowledge and experience in developing websites as digital showcases for MSMEs.